'A New and Fierce Disorder's Raging': Monomania in Mary Barton (1848). (5th March 2019) - Stewart, Lindsey
Abstract: This article examines Elizabeth Gaskell's use of the early psychiatric idea of monomania in her novel Mary Barton (1848). Digital searches show a steep rise in the textual use of the word so that by the mid-1830s it might be described as popularly familiar, albeit still invested with the esotericism and prestige of medical vocabulary. The furore in the press circulating around monomaniacal assassins would not have escaped Gaskell's notice as she began the novel, which was written intermittently between the years 1844 and 1847 and set in c . 1834 to 1840. John Barton, and his sister-in-law, fallen woman Esther, are gripped by obsessive, avenging missions fostered by the pathogenic environments they inhabit. Their trajectories are similar: the loss of a child, a recourse to opiates and alcohol to manage misery and hunger, and an expulsion from the normalizing world of domesticity. The narrative describes both as monomaniacs. I argue that these monomanias are equivalent to a tormenting class consciousness wherein their over-abundant imaginations refuse to accept their lot. A challenge to the notion that the working class were morally at fault, monomania is presented as a condition caused by an environment that can only foster despair. The text does not simply pathologize the characters, but presents the social structure itself as pathological. Gaskell uses a gothic formulation of the disease as 'haunting' and 'incessant'. It is a novelistic version which is both proto-sensational in the projects its sufferers pursue (murder and detection) whilst also signifying a nervous collapse brought about by material deprivation. Gaskell's monomaniacs come closest to replicating the aetiologies of their 'real' counterparts in County Asylums.